Application of smart indoor hydroponic technology to support food security - Yopy Mardiansyah; Nurul Ilmi; Deosa Putra Caniago; Muhamad Abrar Masril; Reant Egie Fahruddini; Hanif Sumardi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Fish provides sufficient animal protein in the island region, particularly Nongsa in Batam City. However, the demand for minerals and vitamins from vegetables is not adequately met. The inefficient use of agricultural land is a major factor in the high vegetable prices in Batam City, reducing community interest in vegetable consumption. The activity aims to address this by introducing a smart indoor hydroponic system to meet vegetable needs. Targeting economically unproductive households, especially in Dasawisma Groups, the activity involves preparation, execution with socialization on the importance of consuming green vegetables and hydroponic tool training, and an evaluation of achievements. The applied technology is smart indoor hydroponic using the Internet of Things (IoT) for nutrient control. All stages of the activity have been successful, improving the group's understanding of green vegetables. Participants can independently operate the hydroponic tool with an automatic nutrient control system and cultivate various vegetables like water spinach and bok choy.